2023
DOI: 10.7759/cureus.37994
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Multicystic Dysplastic Kidney Disease Patients at King Abdulaziz Medical City in Riyadh

Abstract: BackgroundMulticystic dysplastic kidney (MCDK) is a type of kidney dysplasia consisting of many irregular, varioussized cysts divided by dysplastic renal tissue, which negatively impacts kidney function. MCDK is one of the most common renal congenital disorders seen in antenatal ultrasounds. The typical prognosis of MCDK is complete or partial involution that starts antenatally and continues postnatally. The aim of the study was to shed light on the overall outcome of patients with MCDK. MethodsWe retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The previous literature showed variable findings regarding the side of involvement. (5,6,(11)(12)(13) In our series, most of cases (74.3%) were identified antenatal via an ultrasound examination. This rate is comparable with the previous studies.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The previous literature showed variable findings regarding the side of involvement. (5,6,(11)(12)(13) In our series, most of cases (74.3%) were identified antenatal via an ultrasound examination. This rate is comparable with the previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…(16) In contrast to our results, Alamir et al stated that the vast majority (90%) of their cohort showed some degree of involution at a longer follow up period than ours. (13) The previous studies showed that initial MCDK length is the most important factor for predicting complete involution. (22) Hayes et al reported that the involution rates were significantly higher in patients with initial MCDK of <5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic testing is still far from being a part of a regular clinical workup, both in developed and developing countries [4,[61][62][63][64][65]. Therefore, describing the clinical and laboratory findings and outcomes in patients with CyKD can still provide important and valuable information for clinical practice [66]. Nevertheless, due to population genetic and environmental epigenetic influences, single-center cohort studies cannot be generalized [67].…”
Section: Discussionmentioning
confidence: 99%